+0

# HELP QUICK!

+5
101
4
+359

Here are two functions:

If f(10) - g(10) = 10, what is the value of k?

MIRB16  Jul 30, 2017
Sort:

#1
+4710
+4

f( x )  =  3x2 – 2x + 4                    To find  f(10)  , replace every instance of  x  with  10 .

f(10)  =  3(10)2 – 2(10) + 4            Simplify.

f(10)  =  300 – 20 + 4

f(10)  =  284

g( x )  =    x2 – kx – 6                    To find  g(10)  , replace every instance of  x  with  10 .

g(10)  =  (10)2 – k(10) – 6              Simplify.

g(10)  =  100 –10k – 6

g(10)  =  94 – 10k

f(10) – g(10)  =  10                        Replace  f(10)  with 284  . Replace  g(10)  with  94 – 10k  .

284 – (94 – 10k)  =  10                 Now solve for k. Distribute the  -1  to both terms in parenthesees.

284 – 94 + 10k  =  10                  Combine  284  and  -94  .

190 + 10k  =  10                          Subtract  190  from both sides.

10k  =  -180                                 Divide both sides by  10  .

k  =  -18

hectictar  Jul 30, 2017
#2
+1221
+2

Ok, answering this question requires some knowledge of functions.

\(f(x)=3x^2-2x+4\)

\(g(x)=x^2-kx-6\)

When the question asks what is f(10)-g(10), the question is asking what the functions equal to when x=10.

Let's do just that first. I'll evaluate them separately.

 \(f(x)=3x^2-2x+4\) Evaluate the function for f(10), which means make all instances of x into a 10. \(f(10)=3*10^2-2*10+4\) We must be mindful about our order of operations here. First, do the exponent first. \(f(10)=3*100-2*10+4\) Let's evaluate all instances of multiplication first. \(f(10)=300-20+4\) Do the subtraction and addition. \(f(10)=284\)

Now, let's evaluate the other function.

 \(g(x)=x^2-kx-6\) Again, replace all instances of x with 10. \(g(10)=10^2-k*10-6\) Evaluate exponents first to abide with order of operations. \(g(10)=100-10k-6\) Combine the only set of like terms, 100 and -6. \(g(10)=94-10k\)

Ok, now we have to do f(10)-g(10)=10:

 \(f(10)-g(10)=10\) Replace the calculated values for f(10)-g(10) \(284-(94-10k)=10\) Distribute the negative sign into the parentheses. \(284-94+10k=10\) Do 284-94 to simplify the lefthand side. \(190+10k=10\) Subtract 190 on both sides of the equation. \(10k=-180\) Divide by 10 on both sides. \(k=-18\)

Ok, I am done now!

TheXSquaredFactor  Jul 30, 2017
#3
+1221
+1

Wow! We approached the problem in an identical manner, and we explained our method nearly verbatim.

TheXSquaredFactor  Jul 30, 2017
#4
+4710
+2

And...we posted it at almost the exact same time, LOL

hectictar  Jul 30, 2017

### 5 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details